2011
DOI: 10.1530/jme-11-0018
|View full text |Cite
|
Sign up to set email alerts
|

Increased androgen receptor transcription: a cause of castration-resistant prostate cancer and a possible therapeutic target

Abstract: Few effective therapies exist for the treatment of castration-resistant prostate cancer (CRPC). Recent evidence suggests that CRPC may be caused by augmented androgen/androgen receptor (AR) signaling, generally involving AR overexpression. Aberrant androgen/AR signaling associated with AR overexpression also plays a key role in prostate carcinogenesis. Although AR overexpression could be attributed to gene amplification, only 10-20% of CRPCs exhibit AR gene amplification, and aberrant AR expression in the rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
90
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 175 publications
3
90
0
Order By: Relevance
“…Many studies have shown that the progression of CRPC is associated with increased AR expression (Gregory et al 1998, Zegarra-Moro et al 2002, Chen et al 2004, Scher & Sawyers 2005, which can be attributed to gene amplification, transcriptional up-regulation, translational up-regulation, and decreased degradation. As we summarized previously (Shiota et al 2011b (Mizokami et al 1994), and Foxo3a (Yang et al 2005), regulate AR expression. In addition, it has recently been shown that the SREBP-1 transcription factor regulates AR expression (Huang et al 2010), is overexpressed during progression to castration resistance (Ettinger et al 2004), regulates lipogenesis, and induces oxidative stress via NADPH oxidase 5 (Nox5) expression that can be reversed by the Nox inhibitor diphenyliodonium (DPI).…”
Section: Ar Overexpressionmentioning
confidence: 57%
See 1 more Smart Citation
“…Many studies have shown that the progression of CRPC is associated with increased AR expression (Gregory et al 1998, Zegarra-Moro et al 2002, Chen et al 2004, Scher & Sawyers 2005, which can be attributed to gene amplification, transcriptional up-regulation, translational up-regulation, and decreased degradation. As we summarized previously (Shiota et al 2011b (Mizokami et al 1994), and Foxo3a (Yang et al 2005), regulate AR expression. In addition, it has recently been shown that the SREBP-1 transcription factor regulates AR expression (Huang et al 2010), is overexpressed during progression to castration resistance (Ettinger et al 2004), regulates lipogenesis, and induces oxidative stress via NADPH oxidase 5 (Nox5) expression that can be reversed by the Nox inhibitor diphenyliodonium (DPI).…”
Section: Ar Overexpressionmentioning
confidence: 57%
“…AR overexpression is thought to be one of the major causes of CRPC (Shiota et al 2011b). Many studies have shown that the progression of CRPC is associated with increased AR expression (Gregory et al 1998, Zegarra-Moro et al 2002, Chen et al 2004, Scher & Sawyers 2005, which can be attributed to gene amplification, transcriptional up-regulation, translational up-regulation, and decreased degradation.…”
Section: Ar Overexpressionmentioning
confidence: 99%
“…Briefly, a mixture of 2 Â 10 6 LNCaP or VCaP cells were suspended in 0.0375 mL RPMI þ 10% FBS and 0.0625 mL Matrigel/animal and were injected subcutaneously. Once the tumor size reached 200 to 300 mm 3 , the animals were castrated or sham operated, randomized, DHT pellets were implanted subcutaneously or not supplemented, and treated as indicated in the figures. Tumor volume and body weight were measured.…”
Section: Tumor Xenograft Experimentsmentioning
confidence: 99%
“…Overexpression of AR and coactivators drives the growth and metastasis of CRPC even in response to low levels of androgens (3)(4)(5). Despite having castrate levels of serum testosterone, tumor samples obtained from men with CRPC have only a 60% reduction in intratumoral dihydrotestosterone (DHT).…”
Section: Introductionmentioning
confidence: 99%
“…Despite high initial response rates, remissions following ADT are temporary due to the emergence of castration-resistant prostate cancer (CRPC), where AR reactivation occurs and tumors grow in the presence of low levels of androgens. AR activation remains a central mechanism driving CRPC progression (4), involving variable combinations of AR gene amplification, increased AR sensitivity, promiscuous AR-binding mutants, altered expression of coregulators, ligand-independent activation by oncogenic signaling pathways, and increases in androgen biosynthesis (5)(6)(7)(8). These mechanisms likely work in concert to drive CRPC; hence, targeting the AR remains a critical component of novel CRPC therapies (9,10).…”
Section: Introductionmentioning
confidence: 99%